Fences (Paramount Pictures, 2017)
In 1950s Pittsburgh, a Black garbage collector named Troy Maxson--bitter that baseball's color barrier was only broken after his own heyday in the Negro Leagues--is prone to taking out his frustrations on his loved ones.